The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1097/01.olq.0000145855.36181.13
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Audio Computer-Assisted Self-Interviews and Clinician Interviews for Obtaining the Sexual History

Abstract: ACASI sexual histories may help to identify persons at risk for STDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
116
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(126 citation statements)
references
References 38 publications
7
116
1
2
Order By: Relevance
“…Research on computer-assisted interviewing has suggested generally that sensitive behaviors may prompt reticence from informants (Des Jarlais et al 1999; Kissinger et al 1999;Kurth et al 2004), although some studies have found mixed (Perils et al 2004) or negative results (Couper et al 2003). Sexual information may be especially problematic.…”
Section: Implementation Issues In Collecting Network Datamentioning
confidence: 99%
“…Research on computer-assisted interviewing has suggested generally that sensitive behaviors may prompt reticence from informants (Des Jarlais et al 1999; Kissinger et al 1999;Kurth et al 2004), although some studies have found mixed (Perils et al 2004) or negative results (Couper et al 2003). Sexual information may be especially problematic.…”
Section: Implementation Issues In Collecting Network Datamentioning
confidence: 99%
“…However, a growing number of studies indicate higher reporting of sexual risk and drug-using behaviors with computerbased compared to in-person surveys. [46][47][48][49] A recent survey comparing online and offline samples found that the online sample of HIV-negative and never-tested men was significantly more likely to report high risk sexual behavior than were men surveyed offline. 50 Internet-based surveys have the added advantage of eliminating interviewer bias and respondent social desirability bias.…”
Section: Validity Of Datamentioning
confidence: 99%
“…Studies in many domains have demonstrated that computer administration of sensitive questions has been shown to increase reporting levels of sensitive behaviors, particularly in comparison with interviewer-based administration [73,74] as patients prefer and are more willing to disclose sensitive information to a computer rather than an interviewer [74][75][76][77][78][79][80][81][82][83][84][85][86][87]. Direct computer entry further enhances the quality of data by not allowing double or ambiguous answers [88], and it is often associated with a lower rate of unanswered questions than paper forms [80,82,85,88,89] because patients must provide a valid response to a question and/or press the "next" button to move on.Besides computer administration, several other alternatives to interviewer-based collection of adherence information are available. These include paper questionnaires, diaries, interactive voice response (IVR) calls, and text messaging.…”
mentioning
confidence: 99%